Brain Derived Neurotrophic Factor Modification of Epileptiform Burst Discharges in a Temporal Lobe Epilepsy Model - Sanaz Eftekhari; Soraya Mehrabi; Fariba Karimzadeh; Mohammad-Taghi Joghataei; Mojtaba Khaksarian; Mahmoud Reza Hadjighassem; Majid Katebi; Mansooreh Soleimani (Basic and Clinical Neuroscience, 2016)
Introduction: Transforming Growth Factor-Beta 1 (TGF-β1) is a pleiotropic cytokine with potent anti-inflammatory property, which has been considered as an essential risk factor in the inflammatory process of Ischemic Stroke (IS), by involving in the pathophysiological progression of hypertension, atherosclerosis, and lipid metabolisms. -509C/T TGF-β1 gene polymorphism has been found to be associated with the risk of IS. The aim of this meta-analysis was to provide a relatively comprehensive account of the relation between -509C/T gene polymorphisms of TGF-β1 and susceptibility to IS. Methods: Male Wistar rats were divided into sham (receiving phosphate buffered saline within dorsal hippocampus), pilocarpine (epileptic model of TLE), single injection BDNF (epileptic rats which received single high dose of BDBF within dorsal hippocampus), and multiple injections BDNF (epileptic rats which received BDNF in days 10, 11, 12, and 13 after induction of TLE) groups. Their electrocorticogram was recorded and amplitude, frequency, and duration of spikes were evaluated. Results: Amplitude and frequency of epileptiform burst discharges were significantly decreased in animals treated with BDNF compared to pilocarpine group. Conclusion: Our findings suggested that BDNF may modulate the epileptic activity in the animal model of TLE. In addition, it may have therapeutic effect for epilepsy. More studies are necessary to clarify the exact mechanisms of BDNF effects.